PENGARUH ISLAMIC MARKET ORIENTATION, INOVASI PRODUK DAN MODAL SOSIAL TERHADAP KINERJA PEMASARAN UMKM DI KOTA BANDA ACEH - Almalidya Almalidya; Haris Riyaldi (EKSPOLHUM, 2025)
This study investigates the influence of Islamic market orientation, product innovation, and social capital on the marketing performance of MSMEs in Banda Aceh city. The sample used was 99 respondents obtained through the probability sampling technique. The analysis used is multiple linear regression. The results show that, partially, the variables of Islamic market orientation (X1) the t-statistic is 4.213 with a significance level of 0.009, product innovation (X2​) the t-statistic is 6.557 with a significance level of 0.000, which is less than 0.05, and social capital (X3​) the t-statistic is 9.238 with a significance level of 0.000, which is less than 0.05 have a significant positive effect on the marketing performance of MSMEs in Banda Aceh city. Simultaneously, the variables of Islamic market orientation, product innovation, and social capital together influence the marketing performance of MSMEs. This means that the three variables explain 85.2% of the variation in marketing performance. Therefore,to improve marketing performance, MSMEs and related parties should develop more effective strategies by utilizing Islamic market orientation and social capital to carry out product innovation